Recovered changes in the spleen by agmatine treatment after transient cerebral ischemia - Uranchimeg, D (Korean Association of Anatomists, 2010)
Stroke or cerebrovascular injury is the leading cause of disability and the third leading cause of deaths worldwide. After the initial ischemic injury, sympathetic signals are transmitted to the spleen and a compromised blood-brain barrier, coupled with expression of adhesion molecules by the vascular endothelial cells permits an influx of peripheral immune cells. This influx of peripheral immune cells into the brain exacerbates the local brain inflammatory response, leading to enhanced neurodegeneration. Agmatine is a primary amine formed by decarboxylation of L-arginine synthesized in the mammalian brain. In this study, we determined the effect of agmatine on the immune response in the spleen after transient cerebral ischemia. Twenty-three hours after transient cerebral ischemia, the white pulp area was reduced and the number of CD11b(+) macrophages and CD4(+)CD25(+) regulatory T cells (T reg cells) were increased in the spleens in the experimental group as a result of alteration of the immune response in the spleen, as regulated by inflammatory cytokines. In the agmatine treatment group (100 mg/kg IP), the contraction of white pulp was diminished and the number of CD11b(+) macrophages and CD4(+)CD25(+)T reg cells were decreased. Twenty-three hours after transient cerebral ischemia, the brain infarction area was significantly reduced (5.51±1.63% of the whole brain) in the agmatine treatment group compared to 15.02±4.28% of the whole brain in the experimental control group. These results suggest that agmatine treatment can reduce brain infarction through minimizing neuroinflammation and can lessen the danger of post-stroke infection from depression of the immune system after stroke.